Analysis of rational emotional behavioral counseling implementation by counselors to fulfill the meaning of life of students - Aiwani, Aisyiah; Hidayah, Nur; Hambali, IM (Univeritas Papua, 2024)
The Research aims to determine the application of rational emotional behavioral counseling to fulfill the meaning of life of Islamic boarding school students. This research uses a qualitative approach with descriptive analysis methods. The population and sample used in this research were Islamic School at Malang City students who live in Ma'had. From the results of the analysis, it was found that Rational Emotional Behavioral Counseling through the process showed that each individual has various kinds of irrational thoughts in interpreting or carrying out their daily lives which will ultimately cause the individual to confine themselves to wrong life values. Therefore, in the series of rational emotional behavioral counseling, there are ABC-D-EFG stages where the counselor will start by identifying the activating event (A), then the counselor also needs to explore each consequence (C), which is the result of the activating event that the person has counselee. Then, we will also look for problematic beliefs (B) to find points of irrational thinking that will ultimately be dispelled (D) and replaced with new, more rational thoughts. The hope is that the emergence of new thoughts and feelings can bring the value of creativity, experience, and behaving under norms. It can also set new goals for the counselee to understand each goal orientation better.